Posoborowe adaptacje w Mszach Św. z udziałem dzieci - Mariusz Szymański (Wrocławski Przegląd Teologiczny)
The liturgical reinforcement after the Second Vatican Oecumenical Council was very fruitful in many approaches whose aim was to adapt the Liturgy of the Holy Service to the level of development of children who participate there. In the second half of the 20th century after the publication of the Directory for Masses with Children's participation bishops from different countries issued special regulations. They show how to introduce the rules of the Roman Directory in certain local conditions. In some countries there were published special liturgical books, missals and lectionaries about Masses with children. Distinctive changes have been introduced so far, among the others, in Germany, France, Italy, Slovakia, the United States and other English speaking countries. There is a clear answer to the question of using the experiences of those countries in Poland. Priests and religion teachers who want to use the knowledge in the Polish conditions must remember about the priestly advice of the Polish Episcopate of the year 1977. The document shows both the opportunities and the obstacles of adaptation of the Holy Mass for children.